A fluorine-free superhydrophobic coating fabricated by amino acids on soft electroadhesives - Hu, Tan (2025)
Superhydrophobic surfaces are of high importance for generating self-cleaning surfaces that can also prevent corrosion, biofouling, fogging, and icing. Current superhydrophobic surfaces, often based on fluorinated compounds, pose environmental concerns, have high fabrication costs, and exhibit low stability. Herein, we design fluorine-free amino acid-based nanoparticles (SiO2-Phe-Cbz NPs) to fabricate a superhydrophobic coating on elastomers that can be utilized in soft electroadhesive (EA) grippers. The synthesized SiO2-Phe-Cbz NPs are spherical with a diameter of ∼100 nm. Importantly, the synthesized NPs are non-toxic to mammalian cells. The SiO2-Phe-Cbz coating is achieved by spray-coating resulting in a water contact angle of ∼160° and a sliding angle of ∼1°. Notably, the SiO2-Phe-Cbz superhydrophobic coating presents high stability and self-cleaning properties. Furthermore, the coating does not significantly alter the mechanical properties of the elastomers. When applied onto EA grippers, the SiO2-Phe-Cbz coated grippers efficiently handle both dry and wet objects with a quick response, while uncoated EA grippers fail to release the objects in a short time after a voltage cutoff. This work provides a new fabrication method for fluorine-free superhydrophobic coatings by using amino acid as a building block, offering exciting prospects for advancements in superhydrophobic coatings in the application of soft grippers for soft robotics.